Novel tubular switched reluctance motor with double excitation windings: Design, modeling, and experiments - Yan, Liang (2016)
The space utilization of linear switched reluctance machine is relatively low, which unavoidably constrains the improvement of system output performance. The objective of this paper is to propose a novel tubular linear switched reluctance motor with double excitation windings. The employment of double excitation helps to increase the electromagnetic force of the system. Furthermore, the installation of windings on both stator and mover can make the structure more compact and increase the system force density. The design concept and operating principle are presented. Following that, the major structure parameters of the system are determined. Subsequently, electromagnetic force and reluctance are formulated analytically based on equivalent magnetic circuits, and the result is validated with numerical computation. Then, a research prototype is developed, and experiments are conducted on the system output performance. It shows that the proposed design of electric linear machine can achieve higher thrust force compared with conventional linear switched reluctance machines.